PENERAPAN SISTEM MOBILE UGT DALAM MENINGKATKAN FREKUENSI TRANSAKSI DI BMT UGT CABANG GADANG KOTA MALANG - Cita Astri Agustin; Adira Nur Fatikasari; Sherly Eky Pratiwi; Abdillah Ubaidi (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research was conducted using a descriptive qualitative approach. Data was collected through observation and interviews. The data sources for this research are BMT employees in the AOSP and AOAP divisions and BMT UGT Nusantara Capem Gadang customers. The results of this research show that implementing the Mobile UGT system increases the number of transactions carried out at BMT UGT Nusantara Capem Gadang. This method is based on theories about service quality indicators, such as accountability, transaction efficiency, customer assistance, service security, ease of use, and performance. However, there is an obstacle that customers often face, namely the Mobile UGT system which requires a connection to the internet network, if the network is not available then transactions can suddenly fail. The Mobile UGT system also helps institutions synchronize field data with that in the system. The number of customers and transaction frequency increases every year showing customer interest in Mobile UGT.